Spotlight on research integrity: international insights on strengthening research culture in the forensic sciences and beyond - Zoë Hammatt (Oxford University Press, 2021)
Video Abstract Watch the video on Vimeo © 2022 Zoe Hammatt. Published by Informa UK Limited, trading as Taylor & Francis Group